(untitled) (International Journal of Atharva, 2025)
This study examines the impact of academic stress and sleep quality on undergraduate students in Nepal. Using a quantitative, descriptive research design, data were collected from 384 students via a structured questionnaire. Findings indicate high stress levels due to academic workload, with 46.1% frequently experiencing nervousness and 49.7% feeling a lack of control. Poor sleep quality was reported by 38.5%, leading to headaches and irritability. Female students exhibited slightly higher stress levels. The study highlights the strong link between stress, sleep disturbances, and academic performance, emphasizing the need for institutional support and stress management initiatives.